KESULITAN MAHASISWA PRAKTIK PENGALAMAN LAPANGAN BIMBINGAN DAN KONSELING KEPENDIDIKAN DALAM PEMBERIAN LAYANAN INFORMASI - Jeras, Panji; KASIH, FITRIA; YANDRI, HENGKI (Bimbingan dan Konseling, 2014)
PPLBKS or the education guidance and counseling field exsperiencepractis is one of the academic programs obliged to STKIP students which still faces many difficulties it its implementation. The source of difficulty comes either from students themselves or the school environtment. The research purpose is to describe studentsâ difficulties in 1) information service planning, 2) information service realization, 3) information service evaluation. The research is grouped to descriptive research with the population of all students undertaking PPLBKS in odd semester 2013-2014 amounting to 142 students. The research sample is 31 students using proportional random sampling technique. The instrument of collecting data is questionnaire whereas data analysis uses criterion sturgess. The research result shows that the studentsâ difficulties during PPLBKS in information service planning are pretty much in category, in realization are pretty much in category and in evaluation are also pretty much in category. Therefore in every stage of information service, the students face quite many difficulties. Based on the research, it is recommended that the guidance and counseling students facing difficulties in the program in order to adapt themselves with environment in carrying out the education field experience practice.